I. The Impact of Digital Economy Development in BRI Countries on China’s OFDI - Guo, Yue; Zhang, Juyong (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
With the development of the digital economy, the country's production and operation have undergone earth-shaking changes. The digital economy is promoting the transformation of traditional manufacturing to digital and intelligent, giving birth to new industries and models, reducing production costs, improving efficiency in all aspects, and promoting the economic development of the country. In addition, with the implementation of the "Belt and Road" Initiative, the cooperation between China and the "Belt and Road" has become increasingly close, and the development degree of the digital economy has also been included in the consideration of OFDI. Therefore, the research on the development status of the digital economy in the "Belt and Road" and its impact on China's OFDI has important reference value for enterprises to formulate OFDI strategies and promote China's opening up reference value.